ASSESSMENT OF THE LONGEVITY OF RED CURRANT VARIETIES IN THE ENVIRONMENTS OF LENINGRAD PROVINCE - T. A. Suloyeva (Труды по прикладной ботанике, генетике и селекции)
The longevity of 60 varietal accessions from the red currant collection planted in 1985 and 1986 was studied in the environments of Leningrad Province. The accessions studied have different genetic and geographic origin. It is shown that the greatest longevity was observed in the varieties of domestic breeding and those which had in their pedigree such wild species as Ribes rubrum L., R. petraeum Wulf., R. multiflorum , R. altissimum Turcz. ex Pojark., R. atropurpureum C.A. Mey and R. warscewiczii Janz. Insufficient longevity was characteristic of the varieties of West European breeding - the descendants of the European species R. vulgare Lam.